Reaktualisasi Model Pembelajaran Berbasis Masalah: Upaya Menggugah Siswa dari “Mati Suri” Kepekaan Sosial - Nuryah, Nuryah; Wahyudi, Dedi; Kurniasih, Novita (Tapis: Jurnal Penelitian Ilmiah, 2020)
This paper discusses the result of research related to problem-based learning models. The findings of this study are related to the efforts of improving students' social sensitivity. One of the goals of education is to make the output in this case students become successful people both academically and non-academically and have positive moral values in society. To achieve maximum learning outcomes, an educator can use the problem-based learning model. This problem-based learning model is a learning model that links students with the real world so that they are more sensitive to their social environment. These problems make students think critically to be able to solve the puzzle and can be implemented in their social space.